Mechanical performance of double gated injected metallic looking polypropylene parts - M. A. Costantino; V. Pettarin; A. J. Pontes; P. M. Frontini (eXPRESS Polymer Letters)
The metallic effect obtained by incorporation of metal particles in polymers by injection molding has the advantage of eliminating post-processing techniques reducing production cost and time. Nevertheless, undesired defects in the final appearance of parts are common. In this work PP/aluminum pigments were obtained by direct injection molding and the influence of metallic particles on the aesthetic, morphological and mechanical properties of the parts was assessed. Aesthetic aspects could be improved by manipulating processing conditions: high melt temperatures diminished differential shrinkage and made weld lines less noticeable. Also at high melt temperatures Al particles increased thermal conductivity of PP generating a thicker skin, which combined with an inherent gradient temperature and typical shear stresses developed during injection molding, induced the formation of β-PP phase. Mechanical performance of parts showed to be dependent on PP morphology. Distinct deformation behaviors were seen according to the presence of PP polymorph, β-PP counteracting the detrimental effect of not bonded Al flakes, and making PP-Al moldings to have similar toughness as PP moldings with the added value of metallic looking.